Development of low density polyethylene/ graphene nanoplatelets with enhanced thermal properties - Yusof, MA; Nor Rahman, NH; Siti Zubaidah, Sulaiman; Azizul Helmi, Sofian; Mohd Shaiful Zaidi, Mat Desa; Izirwan, Izhab (IEEE, 2018)
The polymer technologies have evolved due to the vast applications of polymer nanocomposites with improved properties such as mechanical and thermal stability to replace the conventional materials. The aim of this study is to develop low density polyethylene (LDPE) / graphene nanoplatelets(GNP) with enhanced thermal properties. Different loadings of GNP (0, 0.5, 1.0 and 1.5 wt%) were incorporated into the LDPE through melt mixing technique using a twin-screw extruder with the screw speed at 50 rpm to produce LDPE/GNP polymer nanocomposites. The degradation behavior of LDPE/GNP was characterized by thermogravimetric analysis (TGA), while the melting temperature (Tm), recrystallization temperature (Tc) and crystallinity (Xc) of polymer composite were analyzed by differential scanning calorimeter (DSC). The results exhibited that Tc decreased by the incorporation of GNP as compared to the pure LDPE. Degree of crystallinity of LDPE/GNP composites was observed to be lower than the pure LDPE. However, the thermal stability of LDPE was slightly increased with the increased loadings of GNP. The overall test showed the increase thermal properties of LDPE/GNP polymer nanocomposite.